THE UNESCO DECISION ON PREAH VIHEAR TEMPLE DISPUTE BETWEEN CAMBODIA AND THAILAND - Puput Dianrosita Aswan (Universitas Muhammadiyah Yogyakarta, 2012)
THE UNESCO DECISION ON PREAH VIHEAR TEMPLE DISPUTE BETWEEN CAMBODIA AND THAILAND